HISTORICAL ASPECT OF THE DEVELOPMENT OF THE PRINCIPLE OF EQUALITY IN LAW - Kopiyka, Kirill (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to study the historical aspect of the development of the principle of equality in law. Research methods: the chosen topic of scientific research requires the use of various scientific methods and approaches to obtain qualitative results. Therefore, the following research methods were used to solve the tasks: analysis; system method; analytical, etc. Results: the idea of equality, which originated in the ancient world, has undergone a thousand-year evolution of its development and has been increasingly recognized over time. In the political and legal history of mankind, in the works of leading scientists, in constitutions, the process of formation of the idea of equality was gradually underway. The attitude to the principle of equality of people from antiquity to the present day has always been the basis for the creation of different visions of the socio-political system, and depending on whether it was a positive or negative attitude towards it, different concepts based on egalitarianism or, conversely, on elitism arose. It should be noted, however, that some authors point out that from the point of view of modern science, such a picture should be considered as a far-reaching simplification. There is still debate about whether whether the values of freedom and equality are compatible, but the stereotype that identifies them exclusively with the right-wing or left-wing political mainstream, respectively, is rather a thing of the past. Discussion: the principle of equality is the basis of the social state, which, through the enshrinement of social rights in the Constitution, makes it possible to guarantee the essential equality of the individual in society, the individual in the legal order, and the social groups that individuals create for the realization of their personality. The idea of equality is fundamental for any democratic state governed by the rule of law, because it ensures a decent position, regardless of the subjective characteristics of the individual, of every citizen in society. The realization of essential equality requires state intervention in various spheres of public life, acting on the basis of various political and legal means.